Stiffness matrix of non-uniform members including the effect of axial forces - Chaoqi, Deng (1991)
The stiffness matrices of four kinds of non-uniform elastic columns subjected to end moments, end shears, and with or without axial forces are derived through the use of fourth order differential equations. An illustrative example for an isolated column was solved. The results compered well with the results of Timoshenko and Gere for the same column. So the stiffness matrices can readily extended to deal with stability analysis of rigid frames with non-uniform members.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript (photocopy)
Keywords: Matrices; Axial loads